A review of antibody, aptamer, and nanomaterials synergistic systems for an amplified electrochemical signal - Reaño, Resmond L.; Escobar, Erwin C. (Frontiers in Bioengineering and Biotechnology, 2024)
The synergy between biomolecules with inorganic nanomaterials and nanoparticles has been investigated over the past years, primarily to improve biomarker reception, generate signals, and amplify the signals generated. In this paper, several articles on aptamer-based and antibody-based electrochemical biosensors that target antigens were examined. Among the key characteristics identified were the electrochemical platform development, which includes the usage of nanomaterials as electroactive or electrocatalytic labels, crosslinking of the biological agent with inorganic compounds, and electrode coating to provide an electronic source and support efficient electron transfer. A single approach using labeled or unlabeled biological receptors has become advantageous due to its simple architecture and more straightforward application method. However, the dual system approach allows the incorporation of more nanomaterials to boost the signal and add more features to the electrochemical system. The dual system approach uses a capture and reporter probe in a competitive or sandwich detection format. The reporter probe is often labeled by an electroactive or electrocatalytic compound or immobilized in a nanocarrier, resulting in an increase in measured peak current in proportion to the target's concentration. The reported limit of detection and linear range for each platform is presented to assess its efficiency. Generally, the dual system aptasensor showed higher sensitivity, stability, and reproducibility than the immunosensor in comparable settings. The aptasensor showed promising results for the development of point-of-care type applications.